2019
DOI: 10.3390/f10020161
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Different Forest Management Methods on Soil Microbial Communities of a Natural Quercus aliena var. acuteserrata Forest in Xiaolongshan, China

Abstract: One of the aims of sustainable forest management is to preserve the diversity and resilience of ecosystems. Unfortunately, changes in the soil microbial communities after forest management remain unclear. We analyzed and compared the soil microbial community of a natural Quercus aliena var. acuteserrata forest after four years of four different management methods using high-throughput sequencing technology. The forest management methods were close-to-nature management (CNFM), structure-based forest management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…The performance of stand parameters under CTNM (Tables 4-5, Figure 3) indirectly supported this viewpoint because more heterogeneous stand parameters were found where CTNM practices had rapidly modified the stand state. Multiple studies have verified that the greater the heterogeneity, the better the stand quality (de Leso et al 2016, Rehush and Waser 2017, Wan et al 2019 and CTNM is an effective method for improving the quality of plantation forests (He et al 2018). The main reason for our finding was that in Masson pine forest after CTNM, the stand density decreased and, therefore, competition was reduced among the remaining trees for water, nutrients and living space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of stand parameters under CTNM (Tables 4-5, Figure 3) indirectly supported this viewpoint because more heterogeneous stand parameters were found where CTNM practices had rapidly modified the stand state. Multiple studies have verified that the greater the heterogeneity, the better the stand quality (de Leso et al 2016, Rehush and Waser 2017, Wan et al 2019 and CTNM is an effective method for improving the quality of plantation forests (He et al 2018). The main reason for our finding was that in Masson pine forest after CTNM, the stand density decreased and, therefore, competition was reduced among the remaining trees for water, nutrients and living space.…”
Section: Discussionmentioning
confidence: 99%
“…Thinning is an essential forestry practice (Shen et al 2017). Numerous studies and observations have shown that thinning induces a change in the succession and recovery of forests, including stand structure, species composition, and vegetation cover (de Groot et al 2016, Nagel et al 2017, Wan et al 2019. The dynamics of stand states after thinning can be used to understand the mechanisms of CTNM for sustainable forestry.…”
mentioning
confidence: 99%
“…Through the study, Meng et al [35] found that, after forest conversion, it can influence soil bacteria communities. Wan et al [36] studied on the effect of forest management methods on soil bacteria communities; they found that forest management method could affect soil bacteria community and soil nutrient. Different soil bacteria communities can cause differences in litter decomposition rates and thus affect soil nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Soil water content (SWC) was determined by drying method [31] and soil temperature (T) was measured using the soil temperature instrument (Table 1). Soil pH, organic carbon (SOC), total nitrogen (TN), available nitrogen (AN), total phosphorus (TP), available phosphorus (AP), total potassium (TK) and available potassium (AK) were measured; for details of the measurement method, refer to Wan et al [32]. The concentrations of soil microbial biomass carbon (MBC) and nitrogen (MBN) were analyzed by fumigation extraction [33].…”
Section: Soil Microbial Community and Soil Propertiesmentioning
confidence: 99%